Characterization of canine coronavirus spread among domestic dogs in Vietnam - NGUYEN, Dung van; TERADA, Yukata; MINAMI, Shohei; YONEMITSU, Kenzo; NAGATA, Nao; LE, Thanh Dinh Ha; KUWATA, Ryusei; SHIMODA, Hiroshi; MAEDA, Ken (Journal of Veterinary Medical Science, 2017)
Canine coronavirus (CCoV) is an important pathogen that causes enteritis in dogs, but there is no information on CCoV infection in Vietnam. To examine the prevalence of CCoV infection among Vietnamese dogs, 201 serum samples were analyzed by virus-neutralization (VN) test. The results showed that antibody against CCoV-II was present in 87 dogs (43.3%). To detect genes of CCoV, fecal samples collected from 30 diarrheic and 50 healthy dogs were examinated by RT-PCR, confirming that 2 diarrheic dogs and 5 healthy dogs were positive for CCoV. Nucleotide sequences of N-terminal region of spike (S) gene indicated that CCoV strains were divided into two subgenotypes, CCoV-IIa and -IIb, respectively. Furthemore, we succeeded in isolating CCoV/dog/HCM47/2015, the isolate was plaque-purified three times, and 3’-terminal one-third of the genome was analyzed. Interestingly, the plaque-purified virus had a large deletion in ORF3abc and E genes (1,165 nt), and a short deletion in ORF7b gene (60 nt), suggesting that these regions are not necessary for in vitro replication of CCoV. Next, the antigenicity between the isolated CCoV-IIb and the other CCoV-IIa was compared by VN test, revealing that antigenicty of the isolated CCoV is equal or higher than that of the other CCoV. In summary, two subgenotypes of CCoV-II are spreading among Vietnamese dogs. The isolated virus with a large deletion after in vitro passage may be useful for the development of vaccine, owing to its antigenicity and efficient viral growth in vitro.